Abuso incestuoso infantil: o poder judiciário garante a proteção integral da criança vítima? - GUIMARÃES, Sandra Suely Moreira Lurine (Universidade Federal do Pará, 2017)
Incestuous child abuse can already be considered a problem of public health due to its high incidence and the harm caused to the child’s development. The dynamics of this form of violence is complex and involves psychological, social and legal aspects. The present study aims to accomplish an approach on this theme starting from its social and legal interface. We shall argue that incestuous practice can compromise the balanced development of the child and thus deny her condition of subject of desire as well as her condition of subject of rights. In both forms of denial of subjectivity, the child is seen only as an object. Our goal has consisted in analyses how judiciary power brazilian has faced the cases of incestuous abuse, in order to investigate the treatment dispensed to the child victim. We discuss that the criminal model, grounded on punitivism is limited to punish the aggressor, relegating the victim to a secondary plan such that she plays only the role of probatory object in the process. Because of the, we sign that Restorative Justice, being an approach focused in the victim, is in line with Victimology, and is the proper legal model to interrupt this modality of violence. For it cares about repair and mainly because it contributes to the child’s resiliency process.